2011
DOI: 10.1007/jhep01(2011)089
|View full text |Cite
|
Sign up to set email alerts
|

5D UED: flat and flavorless

Abstract: Abstract5D UED is not automatically minimally flavor violating. This is due to flavor asymmetric counter-terms required on the branes. Additionally, there are likely to be higher dimensional operators which directly contribute to flavor observables. We document a mostly unsuccessful attempt at utilizing localization in a flat extra dimension to resolve these flavor constraints while maintaining KK-parity as a good quantum number. It is unsuccessful insofar as we seem to be forced to add brane operators in such… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…[33] to be R −1 ∼ > 600 GeV. Generic non-minimal extensions by boundary terms or quark bulk masses can induce FCNCs at the tree-level, which are highly constrained due to the absence of an RS-GIM mechanism [2]. Hence boundary terms and bulk masses in the fermion sector are typically assumed to be flavor-blind (cf.…”
Section: Fcncsmentioning
confidence: 99%
See 1 more Smart Citation
“…[33] to be R −1 ∼ > 600 GeV. Generic non-minimal extensions by boundary terms or quark bulk masses can induce FCNCs at the tree-level, which are highly constrained due to the absence of an RS-GIM mechanism [2]. Hence boundary terms and bulk masses in the fermion sector are typically assumed to be flavor-blind (cf.…”
Section: Fcncsmentioning
confidence: 99%
“…quarks, leptons, gauge bosons and the Higgs boson which have been observed at the LHC. If the extra dimension is 'symmetric' under the reflection about its midpoint, which may be regarded as the consequence of two throats compactification [2] as shown in Fig. 1, a KK mode carries a definite parity (even or odd), dubbed KK-parity.…”
Section: Introductionmentioning
confidence: 99%
“…The splitting is a unique phenomenon in extra dimension models and it may be responsible for the observed Yukawa hierarchy [135] (also see [136,137] for universal extra dimension (UED) setup) and the proton longevity problem (Adams (2000) [139]) in particle physics.…”
Section: Split Fermion Spin Charge and Other Factorsmentioning
confidence: 99%
“…4 In Ref [21] it has been shown that fermion mass matrices in split-UED induce FCNC's unless the mass matrices are flavor blind, i.e., proportional to the unit matrix in flavor space. The same arguments hold for fermion BLKTs.…”
Section: B Split Universal Extra Dimensionsmentioning
confidence: 99%